(untitled) (Research, Society and Development, 2021)
The work aims to reflect on the habit of young people in making abusive use of sexual stimulants, in addition, it intends to understand the general aspects of young people, their relationship with sexuality and the importance of the role of the pharmacist in the practices of self-medication among young people. It is a bibliographic research with survey of scientific data and systematization of recent national data through a qualitative approach with analysis of scientific documents related to the study. The excessive use of medicines for erectile dysfunction can cause damages to the health of the young people who use them. It is notable that the habit of using such drugs is not related to the existence of an erectile dysfunction but as a recreational way to maintain erection for a longer time.